DEATH LANDSCAPES AND COVID-19 IN THE AMERICAS: NORMATIVE RESPONSES OF THE INTER-AMERICAN COMMISSION OF HUMAN RIGHTS TOWARDS VULNERABILITY-DEATH - Marconi, Claudia; Miranda, Rafael de Souza Nascimento; dos Santos, Isabela Agostinelli [UNESP] (FapUNIFESP (SciELO), 2023)
The article engages with the death landscapes of the Americas’ two largest democracies – Brazil and the United States – during the Covid-19 crisis, offering a conceptual tool entitled vulnerability-death binomial to consider the extent to which a politics of tragedy is a turning point in the ways institutional politics addresses vulnerability and death, emphasizing the work of the Inter-American Commission on Human Rights (IACHR). When analyzing the normative responses of IACHR, no articulation was found between vulnerability and death but, instead, a bifurcation of each. Although it reveals that there is not a normative interplay between vulnerability and death, the bifurcation does not mean a choice between binary paths. While the two democracies have raised institutional challenges, the IACHR deepened certain senses of vulnerability and a normative movement towards death: issues historically absent from the international basic structure and capable of challenging the international justice theory
AS PAISAGENS DE MORTE E A COVID-19 NAS AMÉRICAS: AS RESPOSTAS NORMATIVAS DA COMISSÃO INTERAMERICANA DE DIREITOS HUMANOS EM TORNO DA VULNERABILIDADE-MORTE
Keywords: Death Landscapes; Inter-American Commission of Human Rights; International Basic Structure; Normative Response; Vulnerability-Death Binomial